1989
DOI: 10.1172/jci114226
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin binding to cultured calf adrenal zona glomerulosa cells and stimulation of aldosterone secretion.

Abstract: Endothelins are a group of potent vasoconstrictors whose structure was deduced from genomic DNA. ET-1 was first isolated from culture supernatants from porcine endothelial cells and ET-3 was identified from a rat DNA library. We report on the binding of '25l-ET-1 to zona glomerulosa celis in culture and on its ability to stimulate aldosterone secretion. Cultured calf adrenal zona glomerulosa cells have saturable, high affinity [Kd = 1.00±0.17 X 10`s M (SEM)j receptors which bind ET-1 in a temperature and time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(56 citation statements)
references
References 22 publications
3
51
0
2
Order By: Relevance
“…4) suggests a possible role of ET in the regulation of adrenocortical function, especially in the zona glomerulosa. This is supported by the fact that the addition of ET-1 stimulates aldosterone secretion in vitro from the adrenocortical tissue of various animal species [29, [90][91][92][93][94]. However, no data are available in man.…”
Section: Adrenal Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…4) suggests a possible role of ET in the regulation of adrenocortical function, especially in the zona glomerulosa. This is supported by the fact that the addition of ET-1 stimulates aldosterone secretion in vitro from the adrenocortical tissue of various animal species [29, [90][91][92][93][94]. However, no data are available in man.…”
Section: Adrenal Glandmentioning
confidence: 99%
“…Although the receptor initially identified by the binding study has a higher affinity with ET-1 and ET-2 than ET-3 [90,94,98], thus corresponding to the ETA receptor, another receptor with similar affinity with all the ET family peptides, thus corresponding to the ETB receptor, was found [91]. Recent studies with Northern blot analysis on the expression of ET receptor mRNA showed that the ETB receptor is the predominant form [99,100].…”
Section: Adrenal Glandmentioning
confidence: 99%
“…ETs can also stimulate aldosterone secretion from adrenal cells (5)(6)(7)(8)(9)(10)(11), and aldosterone may, in turn, upregulate ET-1 expression (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have suggested that there is a functional link between ETs and aldosterone. First, ETs (in particular ET-1 and ET-2) have been shown to act via ET(A) and ET(B) receptors as aldosterone secretagogues in vitro and in vivo (5)(6)(7)(8)(9)(10)(11). Secondly, ETs may promote activation and proliferation of adrenal cells (12).…”
Section: Introductionmentioning
confidence: 99%
“…For example, human ET-1 potently (EC 50 <10 nM) constricts isolated vascular rings prepared from arteries and veins of the frog R. pipiens (Poder et al 1991), and the toad Bufo viridis (Doi & Fujimoto 1993). In several species of mammal (Cozza et al 1989, Morishita et al 1989, Belloni et al 1996, Rossi et al 1997, ET-1 stimulates steroidogenesis in dispersed cells from the glomerulosa zone of the adrenal cortex and it has been shown that synthetic human ET-1 stimulates both corticosterone and aldosterone production by perifused frog interrenal slices from the frog R. ridibunda (Delarue et al 1990).…”
Section: Introductionmentioning
confidence: 99%